TRIPLE-ROLES PEREMPUAN PENGELOLA ART SHOP DI PANTAI SINDHU KELURAHAN SANUR DENPASAR SELATAN - Dewi, Putu Ayu Puri Sintya; Mahagangga, I Gst. Agung Oka (JURNAL DESTINASI PARIWISATA, 2016)
Economic demands improve the role of women in public area.  It makes women having double workload on domestic and public area. This study is located in Sindhu Beach, Sanur.. The type of data used is quantitative and qualitative data. Sources of data are primary data and secondary data. Data was collected by observation techniques, in-depth interviews, documentary studies and literature studies. Descriptive data were analyzed qualitatively. These studies find that productive roles are women involved as a worker by open souvenir shop in tourist destination. Women are empowered in decision-making on the management of art shop herself. Reproductive role of women such as cooking, shopping daily needs, washing cloth, cleaning house and babysitting. If they are too busy in art shop, they will buy some food in market for their family and bring their dirty cloth to laundry.  Social or community role of women such as participate in Sindhu Art Market organization, Balinese people organization named ‘banjar’ and women organization in banjar. All the roles can be done because women manage their time well. If they have to participate in banjar activities, they close the art shop because they think the social role in banjar is more important.
Keywords: Triple Roles, Women, Art Shop